Development and implementation of a sequential compaction device to obtain radial graded porosity cylinders. (February 2020) - Trueba, P.; Chicardi, E.; Rodríguez-Ortiz, J.A.; Torres, Y.
Abstract: In this work, a sequential compaction device has been successfully developed and implemented to produce commercially pure titanium cylinders, in which the porosity increases from the core to the surface or vice versa. The radial graded porosity (three concentric layers) have been obtained by conventional powder-metallurgy (PM) route and/or space-holder techniques. In the first way, controlling the sequential and differentiated degree of compaction of the layers, starting from the core of the specimen to the external layer. In the second way, by the control of the nature, amount, size and morphology of the spacer in each layer of the titanium cylinder. This device is interesting for the manufacture of implants, particularly for partial replacements of the cortical bone tissues, which replicates the hierarchical porous structure of the bone tissues. Furthermore, the use of this novel device could be extended to other applications that require materials with radial graded porosity, such as self-lubricated bearings, CO2 capture systems, substrates for catalysis, high efficiency heat sinks and surrogate materials to simulate irradiated nuclear fuel. Particularly, for bone replacement implants, the best result was obtained with the soft gradient porosity design (20, 40 and 60 vol. % of the porosity in the core, inner shell and external shell, respectively) and a size range of the spacer between 100–200 μm. In this context, the titanium cylinders manufactured with sodium chloride (NaCl) as spacer showed a Young's modulus of 26 GPa, and a yield strength of 278 MPa. On the other hand, those obtained with ammonium bicarbonate (NH4 HCO3 ) as spacer presented a Young's modulus of 32.3 GPa and a yield strength of 321 MPa. Both designs present a good biomechanical and biofunctional balance, due to the high mechanical strength provided by the core, and the resolution of the stress shielding by the external layer, which also favours the growth of the bone tissue into the implant, due to the amount, size and interconnection of the pores.